Does the apple fall far from the tree? : Agents of socialization of students' ideological orientations - Boneta, Željko (Array, 2021)
The paper presents the results of a survey that assessed the impact of informal and formal agents of the political socialization (PS) process on a sample of students enrolled at the University of Rijeka (N = 635). The correlation between the participants' ideological self-identification (PIS) and the assessed ideological orientation of their parents (PIO) was analyzed. Students believe that no agent of socialization has even moderately inﬂuenced the formation of their political views and assess the weakest inﬂuence of the formal PS agent – teachers in primary and secondary schools. The participants believe that parents have inﬂuenced their political attitudes more than other agents, but assess this inﬂuence on average as weak, regardless of whether they place their parents in the same or diﬀerent positions on the ideological orientation (IO) scale. Left- and right-oriented participants admit a somewhat stronger inﬂuence of their parents' informal PS than those who rank themselves in the center. Statistically significant correlations between PIS and the perceived PIO were obtained. A small share of participants does not perceive a similarity between their own and their parents' IO and there is a negligible share of those who place their parents in diametrically opposed positions on the scale. The participants who have a greater interest in politics and those from a more politically stimulating environment are more inclined to move away from the political center and their parents' IO. Concordance between family IOs increases with the perception of better relationships with parents.